Sistem Pendukung Keputusan Pemilihan Tenaga Kerja Indonesia (TKI) Berdasarkan Kualitas Untuk Menentukan Tempat Kerja Menggunakan Metode Profile Matching (Studi Kasus: PT Adila Prezkifarindo Duta) - Dasarius Gulo (STMIK Budi Darma, 2020)
In the process of selecting Indonesian Workers (TKI) based on quality at PT. Adila Prezkifarindo Duta is classified as still manual, where there is not yet a system for selecting quality migrant workers so it requires a long time for its assessment and the selection process is less effective. To support decision making in the selection of qualified Indonesian Workers (TKI) to make it easier by using a decision support system. One method used in the selection of qualified Indonesian Workers is the Profile Matching method. The profile matching method is a decision-making mechanism by assuming that there is an ideal level of predictor variables that must be met by applicants, rather than the minimum level that must be met or passed. In the profile matching process a process will be compared between individual competencies into standard competencies so that different competencies can be identified (also called Gap). The smaller the gap produced, the greater the weight value. In matching this profile, the selected TKI candidates are Indonesian Workers who are closest to the ideal profile of a qualified TKI.